2019
DOI: 10.1002/jor.24110
|View full text |Cite
|
Sign up to set email alerts
|

MRI UTE‐T2* shows high incidence of cartilage subsurface matrix changes 2 years after ACL reconstruction

Abstract: Mid-sagittal single slice 2-D UTE-T2* mapping may be an efficient means to assess medial femoral cartilage for subsurface matrix changes early after ACL reconstruction while 3-D assessments provide additional sensitivity to changes in the medial tibial plateau. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Classically, elevated T2 values in cartilage have been considered to represent irreversible damage to the extracellular matrix . Most recently, investigators have demonstrated that T2*, as measured by a multi‐echo UTE technique similar to that used in this study, was significantly elevated in cartilage of injured knees compared with uninjured controls . Based on these results from studies in non‐haemophilic populations with injury or osteoarthritis, we expected to find a positive correlation between increasing T2* relaxation times and worsening joint status.…”
Section: Discussionmentioning
confidence: 54%
“…Classically, elevated T2 values in cartilage have been considered to represent irreversible damage to the extracellular matrix . Most recently, investigators have demonstrated that T2*, as measured by a multi‐echo UTE technique similar to that used in this study, was significantly elevated in cartilage of injured knees compared with uninjured controls . Based on these results from studies in non‐haemophilic populations with injury or osteoarthritis, we expected to find a positive correlation between increasing T2* relaxation times and worsening joint status.…”
Section: Discussionmentioning
confidence: 54%
“…Compared with 2D UTE sequences, 3D UTE sequences have the advantage of reducing through‐plane partial volume effects, which is important for imaging the thin (ie 100–200 μm) and curved OCJ region . Multi‐echo 3D UTE techniques with echo subtraction or T 2 * fitting have been used for this purpose, but there have been problems with low OCJ region contrast and the need for intensive post‐processing . For clinical purposes, an optimal 3D UTE sequence should provide whole joint coverage, show the OCJ region with high contrast, be obtainable in clinically acceptable scan time and require little or no post‐processing.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al [86], using a monoexponential decay model, found that UTE T2* values were more sensitive to matrix degeneration than conventional T2 values based on histologic standards, showing lower UTE T2* values associated with severely degraded cartilage. In a recent study of patients 2 years after anterior cruciate ligament reconstruction, UTE T2* assessment could identify deep articular pathologic abnormalities in subclinical disease that were not evident at conventional MRI [94]. Chu et al [95] showed that UTE T2* values were significantly elevated in patients who had undergone ACL reconstruction with arthroscopically normal articular cartilage and menisci.…”
Section: Ultrashort-te T2* Mappingmentioning
confidence: 99%